Dynamic Characteristics of the Rubber-Tailings Mixture Based on Dynamic Triaxial Test - Huandui Liu; Haiming Liu; Wenyun Ding; Hongtao Xie (Advances in Materials Science and Engineering)
The liquefaction of tailings is a common failure mode under earthquake actions. The traditional treatment measures of waste rubber have the disadvantages of environmental pollution and occupying soil resources. The combined treatment of waste rubber and tailings is very likely to have important engineering application and theoretical value, and the dynamic characteristics of the rubber-tailings mixture (RTM) are essential and indispensable for handling them together. In this paper, the dynamic triaxial test was used to study the dynamic mechanical characteristics of the RTM. The test was divided into 5 groups with 54 valid samples. The effects of the rubber particle size, rubber content, consolidation pressure, pH value, and soaking time on the dynamic characteristics of the RTM were studied and discussed. The results show that the liquefaction cycle number of the RTM is 50% higher than that of tailings, and the particle cluster effect theory of the RTM is put forward. It will provide a theoretical basis and guidance for the treatment of the waste rubber and tailings.